2015
DOI: 10.1002/ajmg.a.37089
|View full text |Cite
|
Sign up to set email alerts
|

The third international meeting on genetic disorders in the RAS/MAPK pathway: Towards a therapeutic approach

Abstract: “The Third International Meeting on Genetic Disorders in the RAS/MAPK Pathway: Towards a Therapeutic Approach” was held at the Renaissance Orlando at SeaWorld Hotel (August 2–4, 2013). Seventy-one physicians and scientists attended the meeting, and parallel meetings were held by patient advocacy groups (CFC International, Costello Syndrome Family Network, NF Network and Noonan Syndrome Foundation). Parent and patient advocates opened the meeting with a panel discussion to set the stage regarding their hopes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Adults with NS require long-term cardiac follow-up, given that a third have cardiac disorders that require either drugs for heart failure or arrhythmias, or have a defibrillator or pacemaker implanted (1). Given the clinical importance there has been significant interest in developing pharmacological treatments for cardiomyopathies in NS and NSML (24). It has been shown that inhibitors of the Akt/mTOR pathway can ameliorate HCM in the NSML model (25,26), whereas, genetic interference with, or pharmacologic inhibition of, MEK/ERK in a NS mouse model suppresses the development of CHD (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Adults with NS require long-term cardiac follow-up, given that a third have cardiac disorders that require either drugs for heart failure or arrhythmias, or have a defibrillator or pacemaker implanted (1). Given the clinical importance there has been significant interest in developing pharmacological treatments for cardiomyopathies in NS and NSML (24). It has been shown that inhibitors of the Akt/mTOR pathway can ameliorate HCM in the NSML model (25,26), whereas, genetic interference with, or pharmacologic inhibition of, MEK/ERK in a NS mouse model suppresses the development of CHD (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…about 5%, the receptor-mediated hyperactivation of the Rasdependent signal transduction pathway is a frequent event in human hepatocarcinogenesis (13)(14)(15)(16). Recently, application of Ras-pathway inhibitors has become an important therapeutic strategy for clinical cancer treatment including HCC (16,17).…”
mentioning
confidence: 99%
“…The RASopathy research and patient advocacy communities have laid the foundations required for the development of clinical trials and possible effective therapies. In biennial RASopathy meetings over the past decade, the development of clinical trials and selection of adequate endpoints has been an important part of the agendas (Korf et al, ; Rauen et al, ; Stevenson et al, ). Individuals with a RASopathy are uniquely positioned to benefit from many of the RAS pathway‐targeted therapies developed for cancer therapy (Rauen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, there are many potential therapeutic options for individuals with RASopathies, and the most effective therapeutic for each individual may be disease-or even genotype-specific. (Korf et al, 2015;Rauen et al, 2010;Stevenson et al, 2016). Individuals with a RASopathy are uniquely positioned to benefit from many of the RAS pathway-targeted therapies developed for cancer therapy .…”
Section: Therapeutic Clinical Trials For Individuals With Rasopathimentioning
confidence: 99%